1999
DOI: 10.1073/pnas.96.6.3059
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-deficient mice are protected from streptozotocin-induced diabetes

Abstract: Streptozotocin (STZ) selectively destroys insulin-producing beta islet cells of the pancreas providing a model of type I diabetes. Poly(ADP-ribose) polymerase (PARP) is a nuclear enzyme whose overactivation by DNA strand breaks depletes its substrate NAD ؉ and then ATP, leading to cellular death from energy depletion. We demonstrate DNA damage and a major activation of PARP in pancreatic islets of STZ-treated mice. These mice display a 500% increase in blood glucose and major pancreatic islet damage. In mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(196 citation statements)
references
References 48 publications
6
180
1
1
Order By: Relevance
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 90%
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 90%
“…In endothelial cells treated with high glucose, as well as in diabetes and hyperglycaemia, a sequence of events has been proposed whereby reactive nitrogen and oxygen species trigger DNA single-strand breaks, which in turn induce the rapid and excessive activation of PARP, an event which quickly depletes the intracellular stores of NAD þ (Soriano et al, 2001;Virag & Szabo, 2002). This depletion slows glycolysis, electron transport and ATP formation, and finally initiates acute endothelial dysfunction and vascular instability (Eliasson et al, 1997;Szabo et al, 1997;Burkart et al, 1999;Pieper et al, 1999a;.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to these cytoprotective functions, overstimulation of PARP is associated with pathophysiological effects resulting from rapid depletion of the intracellular NAD þ and ATP pools; this slows the rate of glycolysis and mitochondrial respiration and leads to cellular dysfunction (Eliasson et al, 1997;Szabo et al, 1997;Zingarelli et al, 1998;Burkart et al, 1999;Oliver et al, 1999;Pieper et al, 1999a, b;Soriano et al, 2001). PARP activation is implicated in the pathogenesis of stroke (Eliasson et al, 1997), autoimmune b-cell destruction (Burkart et al, 1999;Pieper et al, 1999a), shock and inflammation (Szabo et al, 1997;Oliver et al, 1999) and diabetic vascular dysfunction (Soriano et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Also, mice deficient in PARP are resistant to beta cell death mediated by streptozotocin, in spite of DNA fragmentation. The absence of PARP prevents the depletion of the cofactor NAD + and the subsequent loss of ATP [84,[88][89][90] and thus cell death.…”
Section: Beta Cell Toxicity Of Streptozotocinmentioning
confidence: 99%